Patient preferences for asthma management: a qualitative study. Issue 8 (16th August 2020) - Baggott, Christina; Chan, Amy; Hurford, Sally; Fingleton, James; Beasley, Richard; Harwood, Matire; Reddel, Helen K; Levack, William Mark Magnus
Abstract : Objective: Preference for asthma management and the use of medications is motivated by the interplay between lived experiences of asthma and patients' attitudes towards medications. Many previous studies have focused on individual aspects of asthma management, such as the use of preventer and reliever inhalers. The aim of this qualitative study was to explore the preferences of patients with mild-moderate asthma for asthma management as a whole and factors that influenced these preferences. Design: A qualitative study employing qualitative descriptive analysis situated within a constructionist epistemology to analyse transcribed audio recordings from focus groups. Setting: Three locations within the greater Wellington area in New Zealand. Participants: Twenty-seven adults with self-reported doctor's diagnosis of asthma, taking short-acting beta-agonists alone or inhaled corticosteroids with or without long-acting beta2 -agonist, who had used any inhaled asthma medication within the last month. Results: Four key areas described preferences for asthma management. Preferences for self-management: participants wanted to be in control of their asthma and developed personal strategies to achieve this. Preferences for the specific medications or treatment regimen: participants preferred regimens that were convenient and reliably relieved symptoms. Preferences for inhaler devices: devices that had dose counters and were easy to use and portable were important. Preferences for asthma services: participants wanted easier access to their inhalers and to be empowered by their healthcare providers. Participant preferences within each of these four areas were influenced by the impact asthma had on their life, their health beliefs, emotional consequences of asthma and perceived barriers to asthma management. Conclusions: This study illustrates the interaction of the lived experience of asthma, factors specific to the individual, and factors relating to asthma treatments in shaping patient preferences for asthma management. This aids our understanding of preferences for asthma management from the patient perspective. Trial registration number: Australian New Zealand Clinical Trials Registry (ACTRN12619000601134).